Mobile registration system for unimap student - Ng, Sai Keat (School of Computer and Communication Engineering, University Malaysia Perlis, 2015)
Registration System for student UniMAP is implemented as a web-based application that can be accessed by user at any place on anytime as long as there is a mobile phone that can connect to internet. The main objective of this project is to develop a mobile web registration system for student UniMAP to register on mobile without the need to come to the campus. This system have a lot of benefits like reduce the wastage of time, reduce traffic jam during the registration days and avoid messy condition during registration day. To develop this system, it is important to understand web programming, object-oriented techniques and know the best practises of developing high-traffic database-driven website. This project is developed with PHP scripting and Java Scripting language and data is stored in MySQL. In addition, HTML and CSS is used to make the interface to look more attractive. Lastly, Apache is used as the service server. This system is good because it bring a lot of convenient to the user and UniMAP sides. However, due to time problems, this system still can make improvement for the best of all.